The Effect of Governance and Accounting Information Systems on Village-Owned Enterprise Performance in Bengkalis District - Melia Dina Sabilla; Nur Azlina; Suci Nurulita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This study aims to determine and examine the factors that affect the performance of Village-Owned Enterprises (Village-Owned Enterprise). The factors tested in this study are governance and accounting information systems. The source of data used in this study is primary data and data collection is carried out directly using a questionnaire which is measured using a Likert scale. The population in this study were all Village-Owned Enterprise in Bengkalis Regency, amounting to 136 Village-Owned Enterprise. The total sample of this research is 58 Village-Owned Enterprise with 174 respondents. The sampling technique used is purposive sampling, simple random sampling, which holds the position of Village-Owned Enterprise director, Village-Owned Enterprise secretary or treasurer, and Village-Owned Enterprise supervisor. Data analysis was performed using multiple linear regression which was processed with the help of SPSS (Software Platform Offers Advanced Statistical Analysis) version 23 program.